「台湾酒類醸造法梗概 臺灣ニ於ケル酒専賣ニ關スル調查 滿州に於ける高梁酒醸造業」より - (:unkn) unknown (文生書院, 2002)
Tables of contents for Taiwan sakerui jōzōhō kōgai, Taiwan ni okeru sake senbai ni kansuru chōsa.
Digitized material from the supplement to "Taiwan sakerui jōzōhō kōgai. Taiwan ni okeru sake senbai ni kansuru chōsa"
「台湾酒類醸造法梗概 台湾における酒専売に関する調査 満州に於ける高梁酒醸造業」より
Keywords: Liquor laws -- Taiwan; Government monopolies -- Law and legislation; Kaoliang liquor; Distilling industries -- China -- Manchuria; Distilling industries; Liquor laws; China -- Manchuria; Taiwan